Different urban consolidation centre scenarios: impact on external costs of last-mile deliveries - Veličković, Marko; Stojanović, Đurđica; Nikoličić, Svetlana; Maslarić, Marinko (Transport, 2018)
The identification and mitigation of negative externalities from goods deliveries in urban areas are important aspects of sustainable urban development. Previous studies have shown that urban freight consolidation increases the load factor of Delivery Vehicles (DVs), reducing the vehicle-kilometres driven and thus reducing negative freight transport externalities in urban areas. The objective of this paper is to explore the possible impact of the number of Urban Consolidation Centres (UCCs) on the external costs of last-mile deliveries in freight transport and to determine the possible contribution of such consolidation scenarios to external cost mitigation. Therefore, several consolidation scenarios are considered assuming different numbers of UCCs in operation. A new consolidation scheme is proposed with more than one UCC to serve a given city area. Input data are obtained from a roadside questionnaire survey with a sample of 1617 drivers at 9 access roads to an urban area as part of the NOvi Sad TRAnsport Model (NOSTRAM) study. Externalities are calculated using the IMPACT methodology and discussed for different urban freight consolidation options. The best option is identified, and the results indicate that properly planned, organised and managed urban freight consolidation can significantly reduce transport externalities. The main research results showed that all of the proposed consolidation options increase the total driving distance in an urban area. However, some consolidation options significantly reduce the driving distance of less manageable vehicles in last-mile deliveries (long-haul heavy- and light-duty vehicles). Consequently, the external costs ranged from 2108.3 to 5420.5 EUR for the consolidation option, whereas the current state externalities are 2791.4 EUR. Thus, more small UCCs may provide better results than the central centre even in medium-sized cities.First Published Online: 4 Sept 2017